COMMERCIAL BANKS’CASH HOLDINGS BEHAVIOUR IN THE PRE AND POST ECONOMIC RECESSION PERIOD IN NIGERIA: X-RAYING THE DETERMINANTS (Journal of Global Accounting, 2022)
This study to empirically evaluates the effect of the adopted determinants on the cashholdingbehaviour of selected Commercial Banks in the pre and post recession periodof Nigeria. Specifically, it intends to ascertain the extent to which Investing activitiesand Financing activities affect Cash holdings of Systematically Important Banks (SIBs)in the pre and post recession periods of Nigeria. It also intends to determine the extentof relationship between investments of SIBs in Nigeria and the volume of cash held inthe pre and post economic recession periods. Secondary source of data collection wassolely utilised, hence, the adoption of the ex-post facto research design. A total of seven(7) SIBs in Nigeria were purposively sampled, and extracts from their respectivefinancial statements for the pre economic recession (2011 - 2014) and post economicrecession (2015 – 2018) periods duly subjected to relevant analyses using Multipleregression and Spearman Correlation statistical tools. Findings obtained fromanalyses showed that Investing activities and Financing activities have significanteffect on the Cash holdings of SIBs in the pre and post recession periods of Nigeria. Itwas also discovered that there is a significant relationship between investments ofSystematically Important Banks in Nigeria and the volume of cash held by them in thepre and post economic recession periods. The study thus concluded that financial crisismay have changed the cash holding behaviour of SIBs and this is considered to have along term effect. The study therefore recommends that Systematically Important Banks(SIBs) should be accorded reliable assistance by appropriate regulatory agencies intoobserving periodic self assessment of their cash holding choices towards ensuring thatsuch decisions does not in anyway pose significant threat to the organisation’s goingconcern in the future. Also, given the magnitude of interest SIBs have in investment,renewed effort should hence be made at ensuring that such Investments are profitableones pursued at manageable risk levels.
Keywords: Cash holding decisions; Financing activities; Investing activities; Investments; Systematically Important Banks